A Música Coral dos Primórdios do Século XX aos Primórdios do Século XXI: a Composição para Coros e a Performance do Repertório Moderno/Contemporâne - Fernandes, Angelo Jose [UNESP]; Kayama, Adriana Giarola (Univ Federal Goias, 2011)
This paper is a small part of my Doctoral dissertation which is a large study about the practice and sonority in various choral music styles. Focusing on the choral music from the beginning of the 20th century to the present day, and based upon a bibliographical review, this article describes the characteristics of the choral composition and reflects on the performance aspects of the performance of modern and contemporary choral repertoire such as vocal tone color, intonation and non-traditional vocal techniques.
Choral music from the beginning of the 20th century to the beginning of the 21th: the composition for choirs and modern repertoire's performance
Keywords: Vocal music; Choral music; Choral Conducting; Vocal technique; Modern music; Contemporary music